Late Mesozoic granitoids in the Qinling Orogen, Central China, and tectonic significance - Li, Nuo; Chen, Yan-Jing; Santosh, M.; Pirajno, Franco (Earth-science reviews, 2018)
The Qinling Orogen in central China is a complex collage built through the closure of the northernmost Paleo-Tethys and the suturing of the Yangtze and the North China cratons. In this contribution, geochronological, geochemical and isotopic data of Late Mesozoic granitoids are compiled, which in turn allow for a broad overview on their petrogenesis with respect to tectonic regime of the Qinling Orogen. After a magmatic hiatus during 160–195 Ma, extensive Late Mesozoic granitoids were emplaced, with an age range of 108–160 Ma. They are dominated by I-type granites that indicate formation through remelting crustal rocks at mid to lower crustal levels, although the magma temperatures are generally lower than 800 °C. The Sr-Nd-Hf isotopic data have provincial characters, which could be a reflection of regional differences in the compositions of their source rocks, and hence of the deep crust. Late Mesozoic granitoids occur in three pulses without any magmatic quiescence: i.e. 108–125 Ma, 125–140 Ma and 140–160 Ma. There is a marked variation between granitoids aged pre- and post-125 Ma in terms of spatial distribution, petrology, geochemistry and isotopic features. The older suite displays a northward younging trend if taking the Mian-Lue suture as the boundary line. Rocks in this suite are composed of quartz diorite-granodiorite-monzogranite-granite association, and occur widespread between 109°E and 112°E. The younger suite occurs only in the easternmost part of the orogen (between 111°E and 113°E), and is dominated by monzogranite, granite and syenogranite. Compared with the older suite, the younger suite is characterized by evolved composition (with higher silica but lower Al2O3, FeOT, MgO and CaO contents) and involved juvenile crust. The magma has a much shallower source as evidenced by low Sr/Y ratios and pronounced Sr, Ba and Eu negative anomalies. The above features indicate that the Late Mesozoic tectonic regime of the Qinling Orogen was an integrated effect of post-collisional compression-extension transition, the back-arc extension related to paleo-Pacific subduction and/or a Cretaceous Pacific superplume event. •Granitoids aged 108–160 Ma occurred in Qinling, with no volcanic equivalents.•Pre- and post-125 Ma granitoids show sharp geochemical and isotopic distinction.•Adakites are restricted to the northernmost part of Qinling during 125–140 Ma.•Highly fractionated I-type occur in the easternmost part during 108–125 Ma.•Paleo-Pacific subduction overprinted Paleo-Tethyan post-collision since 125 Ma.